School Curriculum Administration of Schools under the Nan Primary Educational Service Area Office 2 - Pathumpairot, Kraisorn; Malaitao, Thararat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to: 1) study the condition of school curriculum administration of schools under the Nan Primary Educational Service Area Office 2, and 2) compare curriculum administration conditions. A sample were 310 schools administrators and teachers under the Nan Primary Educational Service Area Office 2. A research tool was a questionnaire with a confident value of 0.97 Data were analyzed using percentage, mean, standard deviation and F-test statistic.The results showed that 1) conditions of school curriculum administration as a whole were at the highest level, when considering each aspect, it found that an aspect with the highest mean was creating school curriculum, followed by supervision, monitoring and evaluation. An aspect with the lowest average was conclusion and report writing, and 2) comparison of the conditions of school curriculum administration, it found that the size of schools and other aspects were not different.